ANALISIS NILAI-NILAI AGAMA DAN MORAL DALAM TAYANGAN UPIN IPIN SEASON 5 IKHLAS DARI HATI PADA ANAK KELOMPOK A DI RA MAMBAIL FALAH - Rosida; Warih Windasari, Indriana (LPPM IAD Probolinggo, 2024)
The aim of this study is to explore and elucidate the religious and ethical principles conveyed in the Upin Ipin season 5 episode titled